2017
DOI: 10.1093/jac/dkx024
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of blaSHV-12-carrying Escherichia coli clones and plasmids from human, animal and food sources

Abstract: Results from this study suggest that the dissemination of bla SHV-12 genes occurs by vertical (clonal) and horizontal transfer, the latter mainly mediated through IncI1 multidrug-resistance plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 34 publications
6
34
1
Order By: Relevance
“…Our results are in agreement with previous studies conducted in Spain reporting low to moderate (1.3%-10%) prevalence of ESBL/AmpC-producing E. coli genes in wild mammals [19]. In particular, in that study, hedgehogs, deer and minks were found as reservoirs of bla CMY-2 and bla SHV-12 E. coli variants [19,27]. However, in the present study new gene variants bla CTX-M-3 , bla SHV-1 , bla SHV-11 , bla SHV-28 and bla SHV-167 , are reported in wildlife.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with previous studies conducted in Spain reporting low to moderate (1.3%-10%) prevalence of ESBL/AmpC-producing E. coli genes in wild mammals [19]. In particular, in that study, hedgehogs, deer and minks were found as reservoirs of bla CMY-2 and bla SHV-12 E. coli variants [19,27]. However, in the present study new gene variants bla CTX-M-3 , bla SHV-1 , bla SHV-11 , bla SHV-28 and bla SHV-167 , are reported in wildlife.…”
Section: Discussionsupporting
confidence: 93%
“…Studies performed in the Iberian Peninsula in wildlife, have reported bla CTX-M-1 as the main ESBL gene circulating [19,26]. Additionally, bla CTX-M-14a and bla SHV-12 have also been frequently detected in E. coli from wild animals [12,27-29] with bla CTX-M-15 described in a recent study carried out in wild birds in Tunisia [17]. Interestingly, in the present study, bla CTX-M-1 and bla CTX-M-14a were never detected, whereas bla CMY-2, bla SHV- 12 and bla CTX-M-15 were frequently isolated not only in E. coli but also in K. pneumoniae and C. freundii isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, this gene cassette was observed in the class 1 integron of Escherichia coli isolates (Alonso et al . ). However, the occurrence of the same gene cassettes in different species suggests the transferability of gene cassettes among the intra and interspecies level and the distribution of antimicrobial resistance genes among the bacteria were by horizontal gene transfer mechanism (Severino and Magalhaes ; Chang et al .…”
Section: Resultsmentioning
confidence: 97%
“…The gene bla CTX-M-14 was less frequent in Europe, but in Asia among the most common ESBL genes in poultry, companion animals, and humans (24). The ESBL gene bla SHV-12 was not frequently reported but was identified in ESBL-producing E. coli from poultry, dogs, and wild birds in Spain and Germany (39). Worldwide, the most common ESBL gene in E. coli isolates of human origin is bla CTX-M-15 , which is mainly associated with the pandemic E. coli clone O25:H4-ST131 (40).…”
Section: Clavulanic-acid Inhibited Class a Esblsmentioning
confidence: 99%